Pendidikan Karakter Berbasis Nilai Ahlussunnah Waljamaah (Studi Kasus di MTs Ma’arif NU Kemiri, Purworejo) - Hanan, Uan Abdul (QUALITY, 2021)
Character education is important in Indonesia, to answer the problem of worrying national character. Among nahdliyin character education is based on the values of ahlussunnah waljamaah. Research on MTs Ma'arif NU Kemiri Purworejo is intended to reveal the application of aswaja values in character education to students. This field research is qualitative by using observation, interview documentation in data collection and Habermens theory for data analysis. The results of the study found that the cultivation of aswaja values (tawassuth, i'tidal, tasammuh, ishlahiyyah and tathowwur) was carried out thoroughly from planning, implementation and evaluation. Character education based on ahlussunnah waljamaah values is carried out sequentially through habituation strategies, introduction of knowledge of goodness, introduction of love of virtue, uswah hasanah, and academic and non-academic repentance.